2019
DOI: 10.3390/pr7060354
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Pressure Fluctuation and Unsteady Flow in a Centrifugal Pump

Abstract: A pump is one of the most important machines in the processes and flow systems. The operation of multistage centrifugal pumps could generate pressure fluctuations and instabilities that may be detrimental to the performance and integrity of the pump. In this paper, a numerical study of the influence of pressure fluctuations and unsteady flow patterns was undertaken in the pump flow channel of three configurations with different diffuser vane numbers. It was found that the amplitude of pressure fluctuation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 34 publications
(38 reference statements)
1
32
0
Order By: Relevance
“…By comparing the pressure at the outlet with different time steps, it was found that small variations exist among the results when using different time steps. Based on this study on the influence of time steps on the solution, 1/60 T (4.54 × 10 −4 s) is selected as the time step for computational efficiency without compromising accuracy [17,18]. The numerical setup is described in Table 3.…”
Section: Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the pressure at the outlet with different time steps, it was found that small variations exist among the results when using different time steps. Based on this study on the influence of time steps on the solution, 1/60 T (4.54 × 10 −4 s) is selected as the time step for computational efficiency without compromising accuracy [17,18]. The numerical setup is described in Table 3.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…And 60 (17) where , and denote the pressure difference, velocity difference, and height difference obtained when the water flow through the pump, M is the torque, and QF is the flow conditions of the self-priming pump. In the analysis and presentation of results, the head and flow conditions are converted into the dimensionless parameters given below [24]: 60 (18) .…”
Section: Hydraulic Performance Of the Pumpmentioning
confidence: 99%
“…In process machinery, pumps, valves, pipes, absorption tower, fluid-bed and other devices which involve complex flow or heat transfer are indispensable [1][2][3][4][5][6][7][8][9][10][11][12][13]. Among them, the valve is an important controlling device for opening and closing pipelines, adjusting the flow direction and regulating the transmission of the medium [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Boncinelli, et.al [6] analyzed the effects of the meridional channel geometries and the blade turning angles of a bowl-type diffuser for a low specific-speed pump to achieve an optimal configuration. Bai, et.al [7] investigated the effect of diffuser vane numbers on the performance of a centrifugal pump with a diffuser and concluded that a lower number of diffuser vanes is beneficial to obtain a good pump stability. It should be stated that some critical geometrical parameters of the diffuser are not mentioned, such as the wrap angles and the vane positions of the diffuser.…”
Section: Introductionmentioning
confidence: 99%